Association Between Membranoproliferative Glomerulonephritis and Colorectal Cancer - A Case Report - Severova Andreevska, Galina; Karanfilovski, Vlatko; Naunovska, Ljupka; Suleyman, Sabir; Shterjova Markovska, Zhaklina; Gjorgjievski, Nikola; Severova, Ana Stojanoska; Dzekova Vidimliski, Pavlina; Ristovska, Vesna; Rambabova Bushljetic, Irena; Arsenkov, Ljuben; Petrushevska, Gordana (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2024)
Membranoproliferative glomerulonephritis (MPGN) is a rare glomerular disease characterized by mesangial hypercellularity and thickening of the glomerular basement membrane (GBM). MPGN can be idiopathic or associated with malignancy, systemic immune complex disorders and chronic infections. It has rarely been associated with solid organ tumors, such as lung, gastric, breast or prostate cancer. We report a patient with MPGN and coexisting colorectal carcinoma. A 48-year-old man presented with anemia, loss of weight, hypertension, and nephrotic syndrome. The renal biopsy findings were compatible with type 1 MPGN. The antineutrophilic cytoplasmic antibodies, antinuclear antibodies, anti-GBM, serologic markers of hepatitis B and hepatitis C and tumor markers were negative. After ruling out the secondary causes of MPGN, the patient was treated with pulse doses of methylprednisolone and a single dose of cyclophosphamide. However, due to the worsening anemia and rectal bleeding, a colonoscopy was performed, which established a diagnosis of adenocarcinoma of the descending colon. The patient was treated with left hemicolectomy and oral corticosteroids. Within a year after the cancer treatment, the patient experienced a complete resolution of the proteinuria and improvement of the kidney function. Although rare, MPGN can be associated with hematologic malignancies and solid organ tumors. The most common causes of secondary MPGN should be ruled out before starting specific treatment. In our patient, cancer treatment has led to a subsequent remission of the nephrotic syndrome, which indicated that this association was not coincidental but rather causal. In patients with a tumor and concomitant glomerulopathy which is suspected to be paraneoplastic in etiology, the treatment of the underlying malignancy should be prioritized.
Keywords: Membranoproliferative glomerulonephritis; nephrotic syndrome; colorectal carcinoma